Perancangan Aplikasi Customer Relationship Management untuk Meningkatkan Pelayanan pada Rumah Sakit St. Carolus - Joni Suhartono; Ardyan Valentino Cahyadi; David Yunus (ComTech: Computer, Mathematics and Engineering Applications, 2015)
Research aims to create a draft of application based on customer relationship management (CRM) toimprove services on St carolus hospital in terms of criticism-suggestions, to create scheduling events and patient schedule for second time which is still less control. Research used survey, interview the parties concerned, aswell as analyzing the systems running on St Carolus hospital. Results of the research are application design that helps to improve the quality of the hospital service to the patient, application design that helps management in holding the event, and managing the input given by the visitor at ease. In conclusion, the application designhelps manage criticism and suggestions, make events, and intertwine relations with patients after medication or treatment.